2020
DOI: 10.1039/d0tc02300k
|View full text |Cite
|
Sign up to set email alerts
|

Entangled light–matter interactions and spectroscopy

Abstract: Entangled photons exhibit non-classical light–matter interactions that create new opportunities in materials and molecular science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 132 publications
0
40
0
Order By: Relevance
“…When molecular vibrational modes are strongly coupled to the cavity modes, they form hybridized quasiparticles–molecular vibrational polaritons. [ 17–40 ] Using a coupled dual‐cavity polariton platform, [ 17 ] we previously demonstrated that nonlinear interactions in the system can be delocalized, through exciting the dark state populations. However, it is insufficient to realize coherence transfer because, unlike dark states, polariton coherences are much shorter lived and are vulnerable to solvent fluctuations across spaces.…”
Section: Introductionmentioning
confidence: 99%
“…When molecular vibrational modes are strongly coupled to the cavity modes, they form hybridized quasiparticles–molecular vibrational polaritons. [ 17–40 ] Using a coupled dual‐cavity polariton platform, [ 17 ] we previously demonstrated that nonlinear interactions in the system can be delocalized, through exciting the dark state populations. However, it is insufficient to realize coherence transfer because, unlike dark states, polariton coherences are much shorter lived and are vulnerable to solvent fluctuations across spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The on-paper measured optical responses exhibited fluctuations as in the samples measured using microcentrifuge tubes. This implies that these fluctuations are not due to any interactions; rather, they are due to the spectrometer conversion process 40 .…”
Section: Resultsmentioning
confidence: 98%
“…2 Rather than by saturating the number of photons in either beam [19], then, we allow the maximization of p f (t) via quantum correlations [49], the potential of which we want to scrutinize here. At an extremum of J[|Φ〉], its functional derivative, (22,23), must vanish,…”
Section: Fluctuation-constrained Optimizationmentioning
confidence: 99%
“…In recent years, the possible use of quantum light sources for quantum-enhanced applications in microscopy or spectroscopy has gathered a lot of attention [18][19][20][21][22][23]. Of particular interest is the use of entangled photon pairs for applications which involve two-photon transitions.…”
Section: Introductionmentioning
confidence: 99%